Masters of health : racial science and slavery in U.S. medical schools - Willoughby, Christopher D. E. (The University of North Carolina Press, 2022)
"Medical science in antebellum America was organized around a paradox: it presumed African Americans to be less than human yet still human enough to be viable as experimental subjects, as cadavers, and for use in the training of medical students. By taking a hard look at the racial ideas of both northern and southern medical schools, Christopher D.E. Willoughby reveals that racist ideas were not external to the medical profession but fundamental to medical knowledge"--